Editorial – Authorship and co-authorship of scientific manuscripts: discussions about criteria for legitimation of co-authorship and parameters of scientific integrity - Vasconcellos, Vinicius Gomes de (2020)
This paper aims to analyze the theme of authorship and co-authorship of scientific articles, especially in relation to Law field of knowledge. Basically, its aim is to answer: when can a researcher legitimately be nominated as coauthor of a scientific paper? This is a pertinent issue, considering the academic, social and economic impacts of the definition of authorship, as well as its importance in terms of accountability and integrity of scientific production. Thus, it will analyze the co-authorship conditions and the basic standards on the subject.